When Does Maluma/Takete Fail? Two Key Failures and a Meta-Analysis Suggest That Phonology and Phonotactics Matter. (August 2017) - Styles, Suzy J.; Gawne, Lauren
Eighty-seven years ago, Köhler reported that the majority of students picked the same answer in a quiz: Which novel word form ('maluma' or 'takete') went best with which abstract line drawing (one curved, one angular). Others have consistently shown the effect in a variety of contexts, with only one reported failure by Rogers and Ross. In the spirit of transparency, we report our own failure in the same journal. In our study, speakers of Syuba, from the Himalaya in Nepal, do not show a preference when matching word forms 'kiki' and 'bubu' to spiky versus curvy shapes. We conducted a meta-analysis of previous studies to investigate the relationship between pseudoword legality and task effects. Our combined analyses suggest a common source for both of the failures: 'wordiness' – We believe these tests fail when the test words do not behave according to the sound structure of the target language.